International management of hazardous wastes - Kummer, Katharina (Clarendon Press,Oxford University Press, 1995)
Uncontrolled transboundary transfer of hazardous wastes was recognized as a major environmental problem in the mid-1980s. The international community responded by elaborating pertinent international agreements. Treaties are now in place at the global and regional levels, and additional ones are being negotiated. Despite their common aim of protecting the environment against the ill-effects of hazardous wastes, they often differ in stringency as well as scope and membership